CONTINUING EDUCATION IN NURSING: THE CASE OF A SCHOOL-HOSPITAL IN MACEIÓ - ALAGOAS, BRAZIL (Fiep Bulletin - online, 2014)
This study presents a reflexive point of view about a Continuing Education Service in a School-hospital in Maceió City, Alagoas State, Brazil, and the performance of its charge nurse. It emphasizes how it is important to respect the service's aims and the need of the institution involvement, as a way of work interchange among them to build a quality service. Looking to the aim of knowing the support given by this Continuing Education Service, the descriptive methodological approach, adopted as a case study, allowed to go further, starting from well defined standards that had influence in the comprehension of the relation among the service nurse and institution, showing the real attribution of the nurse inside the environment where she or he is inserted.
Keywords: continuing education; nursing; school-hospital